Design & Simulation of Dielectric Resonator Antenna for Millimeter Applications - Dr.P. Mital*, Rahul Kumar Paswan* (International Journal of Scientific Research and Management (IJSRM), 2016)
This paper presents the design and simulation of broadband Dielectric Resonator antenna usingHighFrequency Structure Simulator (HFSS). This paper investigate stacked cylindrical DRA,s placed onconcentricannular rings .These hybrid nature of structure is operating under controlled electric fields andmagneticfields. Higher gain has been reported in proposed work when electric bias is given , under magneticbiasbandwidth of the antenna is enhanced by making little bit compromise on the Gain. Frequency shift hasalso been notice during magnetic and electric bias condition .This can be wisely used for gettingreconfigurability.